Emotional Intelligence and resilience in mental health professionals caring for patients with serious mental illness. Issue 6 (17th August 2016) - Frajo-Apor, Beatrice; Pardeller, Silvia; Kemmler, Georg; Hofer, Alex
Abstract : Emotional Intelligence (EI) and resilience may be considered as prerequisites for mental health professionals caring for patients with serious mental illness (SMI), since they are often exposed to severe emotional stress during daily work. Accordingly, this cross-sectional study assessed both EI and resilience and their interrelationship in 61 individuals belonging to an assertive outreach team for patients suffering from SMI compared 61 control subjects without healthcare-related working conditions. EI was assessed by means of the German version of the Mayer-Salovey-Caruso-Emotional-Intelligence Test (MSCEIT), resilience was assessed using the German version of the Resilience Scale. Both groups showed an average level of EI in all categories of the MSCEIT and indicated high levels of resilience. They did not differ significantly from each other, neither in terms of EI nor resilience. Correlation analysis revealed a positive association between EI and resilience, albeit small in magnitude. Our results suggest that mental health professionals are not more resilient and therefore not more 'protected' from stressors than the general population. Though this finding warrants cautious interpretation, the positive correlation between EI and resilience suggests that EI may be a potential target for education and training in order to strengthen resilience even in healthy individuals and vice versa.